2014
DOI: 10.1016/j.pain.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Remembering the dynamic changes in pain intensity and unpleasantness: A psychophysical study

Abstract: This study investigated the short-term memory of dynamic changes in acute pain using psychophysical methods. Pain intensity or unpleasantness induced by painful contact-heat stimuli of 8, 9, or 10s was rated continuously during the stimulus or after a 14-s delay using an electronic visual analog scale in 10 healthy volunteers. Because the continuous visual analog scale time courses contained large amounts of redundant information, a principal component analysis was applied to characterize the main features inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…The underestimation of duration in delayed reproduction that we previously reported with continuous heat pain stimuli (Khoshnejad et al 2014) is hereby shown to generalize to innocuous cool sensation. Interestingly, this underestimation effect was not found with the segmented stimuli for which the duration of the delayed reproduction of the dynamic sensation matched the duration of the concurrent rating of the sensation (Fig.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The underestimation of duration in delayed reproduction that we previously reported with continuous heat pain stimuli (Khoshnejad et al 2014) is hereby shown to generalize to innocuous cool sensation. Interestingly, this underestimation effect was not found with the segmented stimuli for which the duration of the delayed reproduction of the dynamic sensation matched the duration of the concurrent rating of the sensation (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Another factor adding some complexity to the interpretation of the present results in relation to the time perception literature is the delay between the stimulus offset and the interval reproduction. The inclusion of this delay was motivated by our previous observation that both the intensity and duration of heat pain sensations appear to be distorted in short-term memory (Rainville et al 2004;Khoshnejad et al 2014). Some of the effects reported here may be associated with memory processes that might have less impact in the immediate reproduction or discrimination tasks typically used in prospective time perception studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…b.Location of pain: Pelvis, lower abdomen, low back, medial aspect of thigh, inguinal area, perineum. c.Perception of pain: Patients may describe the pain as sharp, burning, aching, shooting, stabbing, pressure or discomfort, sexual pain (dyspareunia) d.Modality of pain (7): Persistent and/or continuous, recurrent and/or episodic and/or cyclic (related to menstrual cycle). …”
Section: Taxonomymentioning
confidence: 99%